2015
DOI: 10.1021/acs.langmuir.5b02761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Self-Assembled Monolayers on Thin-Film Morphology: A Combined DFT/MD Simulation Protocol

Abstract: Organic thin film transistors (OTFTs) are multilayer field-effect transistors that employ an organic conjugated material as semiconductor. Several experimental groups have recently demonstrated that the insertion of an organic self-assembled monolayer (SAM) between the dielectric and the semiconductive layer is responsible for a sensible improvement of the OTFT performances in terms of an increased charge carrier mobility caused by a higher degree of order in the organic semiconductor layer. Here, we describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…In order to model a realistic SAM surface, a computational protocol inspired by Ref. 49 , herein described, was adopted. All the periodic density functional theory (DFT) calculations were performed using the CP2K/Quickstep package 50 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to model a realistic SAM surface, a computational protocol inspired by Ref. 49 , herein described, was adopted. All the periodic density functional theory (DFT) calculations were performed using the CP2K/Quickstep package 50 .…”
Section: Methodsmentioning
confidence: 99%
“…7 This is mainly because SAMs provide a convenient strategy to control the physical, chemical, and electronic properties of surfaces of metals and inorganic semiconductors. 7 For applications in electronics, SAMs have been used to lower charge injection barriers, 8 to improve packing of polymers and small molecules in organic thin lm transistors, 9,10 and as the active component in SAM-based molecular electronics. 7,[11][12][13][14][15][16] One of the advantages of SAMs in these applications is that they can be chemically tailored, allowing for atomic scale control over the electronic structure of the molecule-electrode interfaces, which, in turn, determines the performance of the SAM-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…The (010) surface was selected because previous studies have already shown that it is the most stable, 50 and, moreover, it has been successfully used to analyze the insertion of phosphonic acids. 51 The proposed mechanism involves the protonation of one of the OH groups of the supercell by the squaramic acid (or carboxylic acid) and a subsequent replacement of water by the squaramate (or a carboxylate) anion though a coordination bond to two Al-atoms. For the theoretical studies, we have used squaramic acid 4 and butyric acid as models.…”
Section: Resultsmentioning
confidence: 99%